Ron Clark's methods for working with students with low academic performance Xatamova Z. - Xatamova Z (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Taking into account that only some approaches to assisting low achievers in learning more successfully have been systematically studied to determine their effectiveness, this article summarizes what Ron Clark's methods research will assist low achievers in improving performance at learning.